METHODS AND COMPOSITIONS FOR DIAGNOSIS AND PROGNOSIS OF RENAL INJURY AND RENAL FAILURE - JOSEPH ANDERBERG; PAUL MCPHERSON; NAKAMURA KEVIN; JEFF GRAY (2016)
PROBLEM TO BE SOLVED: To provide methods and compositions for monitoring, diagnosis, prognosis, and determination of treatment regimens in subjects suffering from or suspected of having a renal injury.SOLUTION: The present invention relates to use of assays that detect one or more markers selected from a group consisting of soluble P-selectin, protein NOV homolog, soluble epidermal growth factor receptor, netrin-4, haptoglobin, heat shock protein β-1, α-1-antitrypsin, leukocyte elastase, soluble tumor necrosis factor receptor superfamily member 6, soluble tumor necrosis factor ligand superfamily member 6, soluble intercellular adhesion molecule 2, active caspase-3, and soluble platelet endothelial cell adhesion molecule as diagnostic and prognostic biomarkers in renal injuries.SELECTED DRAWING: None 【課題】腎損傷を患っている対象または腎損傷に罹っている疑いのある対象における監視、診断、予後、および治療計画の決定のための方法ならびに組成物を提供する。【解決手段】腎損傷における診断および予後のバイオマーカーとして、可溶性Ｐ−セレクチン、タンパク質ＮＯＶホモログ、可溶性上皮増殖因子受容体、ネトリン−４、ハプトグロビン、熱ショックタンパク質β−１、α−１−アンチトリプシン、白血球エラスターゼ、可溶性腫瘍壊死因子受容体スーパーファミリーメンバー６、可溶性腫瘍壊死因子リガンドスーパーファミリーメンバー６、可溶性細胞間接着分子２、活性型カスパーゼ−３および可溶性血小板内皮細胞接着分子からなる群から選択される１以上のマーカーを検出するアッセイを使用する。【選択図】なし